THE ADVANCED ELECTRIC FIELD FROM QUAD-ELECTRODE MODE FOR BLOOD CANCER TRAPPING: SIMULATION STUDY - Miftakhul Firdhaus; Ulya Farahdina; Vinda Zakiyatuz Zulfa; Ahmad Ridlo Hanifudin Tahier; Mohammad Haekal; Endarko Endarko; Darsono Darsono; Agus Rubiyanto; Nasori Nasori (Jurnal Sains Materi Indonesia, 2022)
THE ADVANCED ELECTRIC FIELD FROM QUAD-ELECTRODE MODE FOR BLOOD CANCER TRAPPING: SIMULATION STUDY. Blood cancer is a disease caused by the rapid cleavage of white blood cells (WBC), which increases in the human circulatory system. Furthermore, based on the original nature of WBC during cleavage, which is the same as ionic bonds, electric field filtering, and trapping is used to treat leukemia patients. The electric field generated by the electrode with an AC voltage source plays a role in the migration of the WBC to high electric field intensity. The Quad-electrode field distribution is conducted using the Finite Element Method (FEM), and an electric field gradient analysis is conducted to determine the effectiveness of each coordinate system. According to the simulation results, the second model with an input voltage of 0.68 V has the highest intensity of electric field distribution, with an effective depth at Z = 30 mm, and the best coordinate along the X-axis and Y-axis are 30 mm. In conclusion, the center of the Quad-electrode system center is the best location for placing filters and trapping leukocytes by utilizing electric field distribution on the electrode system for the development of blood cancer biomedical therapy technology.